Perceived Life Outcomes of Indian Children During the Early Phase of the COVID-19 Lockdown: The Protective Roles of Joint and Nuclear Families - Gyanesh Kumar Tiwari; Raghavendra Prasad Tiwari; Rakesh Pandey; Bablu Ray; Abhigyan Dwivedi; Devaki Nandan Sharma; Pankaj Singh; Ajay Kumar Tiwari; Ajit Kumar Singh (Gonabad University of Medical Sciences, 2024)
Background: Although many negative consequences of the COVID-19 pandemic are reported for adults, little is known about its impacts on children, especially in terms of the relative roles of joint and nuclear families. Using a qualitative design, we explored the protective roles of joint and nuclear families in shaping the children's life outcomes during COVID-19.  Methods: In a qualitative study, 16 full-time mothers of children aged 9-12 years (8 each from joint and nuclear families) from Sagar City, India were interviewed during June and July 2020. Interview contents were audiotaped, transcribed verbatim, and analyzed using the thematic analysis method. Results: Five major themes were identified, negative impacts of the COVID-19 pandemic, differences in positive engagements, emotional protective benefits, promotion of positive health habits, and routine activity management strategies. The results showed that the joint families availed and utilized more resources to positively engage their children in creativity, studies, exercise, and entertainment during the restrictions of the lockdown compared to the nuclear families. Contrary to the nuclear families, the joint families emphasized resolving emotional grievances, promoting positive emotional engagement, and extending more emotional support to their children. The joint and nuclear families also differed in their children's food habits, health grievances, and physical exercise. Also, the joint families played more positive roles in managing children's play behaviors, sleep habits, television watching, and other children's activities compared to the nuclear families. Conclusion: The distinctive availability of experiential, emotional, relational, and positive value resources and knowledge repertoires of the two family systems may have extended differential protective benefits to their children during the COVID-19 lockdown.